2018
DOI: 10.1093/hmg/ddy356
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of NMNAT2 compromise axon development and survival

Abstract: NMNAT2 is an endogenous axon maintenance factor that preserves axon health by blocking Wallerian-like axon degeneration. Mice lacking NMNAT2 die at birth with severe axon defects in both the PNS and CNS so a complete absence of NMNAT2 in humans is likely to be similarly harmful, but probably rare. However, there is evidence of widespread natural variation in human NMNAT2 mRNA expression so it is important to establish whether reduced levels of NMNAT2 have consequences that impact health. Whilst mice that expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
6
40
0
Order By: Relevance
“…The accompanying paper (Lukacs et al) reports a more severe and lethal phenotype associated with near-complete biallelic loss-of-function of NMNAT2. In common with the T94M phenotype, this is consistent with an axon loss phenotype (or failure of axon growth) affecting multiple neuron types, as also observed in both the complete null and knockdown mice 6,18,28 . The severity of the two human phenotypes correlates well with the degree of loss-of-function with the corresponding models in mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The accompanying paper (Lukacs et al) reports a more severe and lethal phenotype associated with near-complete biallelic loss-of-function of NMNAT2. In common with the T94M phenotype, this is consistent with an axon loss phenotype (or failure of axon growth) affecting multiple neuron types, as also observed in both the complete null and knockdown mice 6,18,28 . The severity of the two human phenotypes correlates well with the degree of loss-of-function with the corresponding models in mice.…”
Section: Discussionsupporting
confidence: 82%
“…All previous data on NMNAT2 mutant phenotypes come from mouse studies where expression is either reduced or ablated. The T94M mutation only partly disrupts the function of NMNAT2, so T94M homozygosity in the patients is arguably more similar to mice with heterozygous levels (~50%) or sub-heterozygous levels (~30%) of NMNAT2, which are viable into old age, than to mice homozygous for a silenced allele where a failure of nerve growth precludes survival 6,28 . Intriguingly, there are strong parallels between the patients described here and mice with sub-heterozygous levels of NMNAT2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that lowering the expression of NMNAT2 increases axonal 135 vulnerability to several stresses (Gilley et al, 2019). To test whether lowering NMNAT2 136 expression impairs the ability to withstand mitochondrial impairment, SCG neurons 137 from mice with around 60% (Nmnat2 +/gtE ) and 30% (Nmnat2 gtBay/gtE ) of wild type 138…”
Section: Introduction 46mentioning
confidence: 99%
“…NMNAT2 localizes to the Golgi and cytosolic compartments and localized exclusively to neurons and hair follicles [ 28 ]. In neurons, NMNAT2 plays a pivotal role in axon development and survival [ 29 , 30 , 31 ] and its depletion can trigger Wallerian degeneration [ 32 , 33 ]. While the role of NAD + in balancing cellular homeostasis is evolutionally conserved [ 34 ], only three pathways that lead to NAD + synthesis have been described (in mammalian cells, the core focus of this review) [ 35 ].…”
Section: Nicotinamide Adenine Dinucleotidementioning
confidence: 99%